Comparative Evaluation of Microleakage in Various Placement Techniques of Composite Restoration: An In Vitro Study - Somani, Rani (Int J Clin Pediatr Dent, 2020)
AIM: The study was conducted to evaluate and compare the effect of various placement techniques of composite restoration on microleakage. MATERIALS AND METHODS: Forty extracted premolars were selected and a rectangular-shaped cavity was prepared on the buccal surface of cervical third of each tooth. Thereafter, teeth were randomly divided into four groups equally and were restored with the composite restorative material with different placement techniques, i.e., bulk placement technique, horizontal incremental technique, split incremental technique, and newly introduced Mat incremental technique. Samples were thermocycled and immersed in methylene blue dye for 24 hours. The samples were then sectioned and evaluated under a stereomicroscope for microleakage. RESULTS: Microleakage was present least in the Mat incremental group and maximum in the bulk placement group while intercomparison revealed statistically significant difference between all the groups except for split incremental and Mat incremental groups. CONCLUSION: The recently introduced Mat incremental placement technique showed least microleakage when compared to conventional techniques. HOW TO CITE THIS ARTICLE: Somani R, Som NK, Jaidka S, et al. Comparative Evaluation of Microleakage in Various Placement Techniques of Composite Restoration: An In Vitro Study. Int J Clin Pediatr Dent 2020;13(3):264–268.